IMPLEMENTASI PEMBELAJARAN AKTIF DALAM HABITUASI HARI BERBAHASA ARAB JURUSAN KEAGAMAAN DI MA DARUL ULUM PURWOGONDO KALINYAMATAN JEPARA - Ismail, Nur Mahmudi (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
The application of active learning in learning Arabic at MA Darul Ulum Purwogondo Kalinyamatan Jepara. The implementation of active learning is learning that is made so that students can take part in learning actively and fun. So that students have many roles in participating when the learning process takes place in order to improve the quality and satisfactory results. This study aims to determine the level of interest of students in Arabic subjects at MA Darul Ulum Purwogondo Kalinyamatan Jepara. This research is a qualitative research. Data collection techniques using the method of observation, interviews, and documentation. Research on the implementation of active learning in Arabic subjects majoring in religion at MA Darul Ulum Purwogondo Kalinyamatan Jepara has been going well by emphasizing Arabic-language students majoring in religion with the concept of an Arabic day every Sunday. In the process of implementing active learning for Arabic subjects, the teacher provided a stimulus or stimulus that aims to be motivated and understand what the learning objectives are to be studied. Active learning is carried out after the educator delivers the material by asking questions to students individually or in groups (if forming groups). Educators also give awards or rewards to groups that can answer questions from educators based on teams that work together correctly and well.